Badhaus: un progetto di recupero urbano nel cuore di Bressanone. Dialogo con Gerd Bergmeister, bergmeisterwolf - Simona Galateo (ArchAlp)
The Badhaus project by bergmeisterwolf is an emblematic example of the dialogue between South Tyrolean architecture and the landscape, tradition, and contemporary needs. This intervention focused on tourism and accommodation in the historic centre of Brixen has triggered an urban transformation based on a design intuition that developed from Othmar Barth’s earlier vision for the same site. The project, which was developed through an extensive dialogue with the neighbouring owners, the administration, and heritage authorities, goes beyond the scale of a single building and redesigns the entire collective space. The result is an urban ‘microsurgery’ capable of repairing an entire piece of the city through new passages, remodelled courtyards, and pathways. The strength of the Badhaus lies in its ability to redefine the relationship between public and private space by generously opening to the city while preserving privacy. This urban permeability is of particular importance in Brixen, a mountain town where buildings and communities often remain self-contained. The choice of materials – stone for communal areas, wood for more intimate passages, plaster for new volumes – reinforces this dialectic between public and private. As Gerd Bergmeister explains, architecture today must physically, socially, and culturally reactivate parts of cities that are in danger of losing their vitality and propose innovative solutions to the challenges of our time.